Factors Associated with Employee Retention Program: An Assessment for Program Improvement - Marpuri, Jessica C. (The Indonesian Institute of Science and Technology Research, 2025)
This study evaluates the employee retention program of Camarines Sur Polytechnic Colleges (CSPC) for the fiscal years 2020–2021, aiming to identify factors influencing retention and areas for improvement. Utilizing a descriptive-evaluative-correlational research design, data were collected from 190 respondents categorized as regular, casual, and job order employees. Key factors, including training attendance, career advancement, compensation, and awards, were found to significantly affect retention, with training ranked as the most influential. Results indicate disparities in access to benefits and development opportunities between regular and non-regular employees, emphasizing the need for equity-focused reforms. Retention strategies, such as morale-boosting activities and performance evaluations, strongly correlate with employee satisfaction. The study recommends enhancing inclusivity, equitable benefit distribution, and continuous professional development programs to strengthen workforce loyalty and reduce attrition. These findings underscore the critical role of sustainable human resource policies in fostering employee satisfaction and institutional efficiency.